2020
DOI: 10.1002/qute.202000042
|View full text |Cite
|
Sign up to set email alerts
|

Probing Proximity‐Tailored High Spin–Orbit Coupling in 2D Materials

Abstract: Proximity‐induced tuning of spin–orbit coupling (SOC) is of paramount importance in emerging magnetic materials and in spintronics. Probing the above SOC via light–matter interaction assisted methods provides a novel route to investigate interesting material phenomena. Here, the proximity studies in a heterostructure of monolayer molybdenum disulfide (MS) and iron (Fe) to enhance and tune the interfacial SOC are reported. The augmented SOC of the MSFe heterostructure arises due to interfacial charge transfer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
(45 reference statements)
2
8
0
Order By: Relevance
“…Indeed, the observed torques in TMD/FM heterostructures cannot always be explained by well-known effects such as the bulk spin Hall effect (SHE) (Dyakonov and Perel, 1971;Hirsch, 1999;Sinova et al, 2015) or the interfacial Rashba-Edelstein Effect (REE) (Edelstein, 1990;Ganichev et al, 2002;Kato et al, 2004;Mihai Miron et al, 2010;Ganichev et al, 2016) (Figure 1), indicating that other mechanisms involving material specific properties or interfacial effects are into play. This is supported by recent works suggesting that both the type of ferromagnetic layer (Dolui and Nikolic, 2020;Go and Lee, 2020) and the interface properties between the TMD and the ferromagnetic layer (Amin et al, 2020;Sousa et al, 2020;Go et al, 2020) (Sahoo et al, 2020;Kumar et al, 2020;Xue et al 2020) are of paramount importance for the observed SOTs, allowing for enhanced and unconventional SOTs.…”
Section: Introductionsupporting
confidence: 68%
“…Indeed, the observed torques in TMD/FM heterostructures cannot always be explained by well-known effects such as the bulk spin Hall effect (SHE) (Dyakonov and Perel, 1971;Hirsch, 1999;Sinova et al, 2015) or the interfacial Rashba-Edelstein Effect (REE) (Edelstein, 1990;Ganichev et al, 2002;Kato et al, 2004;Mihai Miron et al, 2010;Ganichev et al, 2016) (Figure 1), indicating that other mechanisms involving material specific properties or interfacial effects are into play. This is supported by recent works suggesting that both the type of ferromagnetic layer (Dolui and Nikolic, 2020;Go and Lee, 2020) and the interface properties between the TMD and the ferromagnetic layer (Amin et al, 2020;Sousa et al, 2020;Go et al, 2020) (Sahoo et al, 2020;Kumar et al, 2020;Xue et al 2020) are of paramount importance for the observed SOTs, allowing for enhanced and unconventional SOTs.…”
Section: Introductionsupporting
confidence: 68%
“…The SHEL creates spatial separation between opposite chiralities of light when a polarized light beam is reflected by a surface. In SHEL-based reflection measurements, appropriate selection of polarization pointer states before and after the reflection of a Gaussian light beam enable one to enhance the signals significantly due to the interaction of light with the samples (MS and VMS) [23]. The complex optical beam shift happens due to the spin-orbit interaction of light with the material and the changes in the underlying geometric phase [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In SHEL-based reflection measurements, appropriate selection of polarization pointer states before and after the reflection of a Gaussian light beam enable one to enhance the signals significantly due to the interaction of light with the samples (MS and VMS) [23]. The complex optical beam shift happens due to the spin-orbit interaction of light with the material and the changes in the underlying geometric phase [23][24][25][26]. This allows the quantification of chirality-dependent absorption, and polarization rotation due to interaction with material more precisely [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The MSPy films developed are now investigated for the changes arising due to SOC by leveraging on the weak amplification-assisted SHEL-MOKE technique. MoS 2 , being a high SOC material, in proximity to the ferromagnetic materials, modulates the magnetic ordering at the interface due to possible charge/spin transfer [21]. Using SHEL-MOKE, we observe this modulation in the magnetic ordering of the permalloy in proximity to MoS 2 as a significant enhancement in the observed coercivity in the P-MOKE configuration.…”
Section: Resultsmentioning
confidence: 77%
“…The SHEL is an archetypical example of the WM method, arising due to spin-orbit interaction (SOI) with underlying geometric phase [18], and has revolutionized optical measurements, enabling extremely high precision measurements [14,19,20]. Recently it was shown that SHEL measurements offer a new method to probe magnetic ordering in finite-sized 2D crystals [21]. We expand on the basic idea to show that WM-based investigation is also suitable to measure the complex optical beam-shift to characterize and quantify the magnetization, coercivity, spin-orbit coupling strength, and the optical conductivity arising at the surface and interface of ultra-thin film samples.…”
Section: Introductionmentioning
confidence: 99%